2015
DOI: 10.3928/01477447-20150603-59
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Urinary Retention in Men Undergoing Total Hip Arthroplasty

Abstract: Postoperative urinary retention is a common complication after major orthopedic procedures of the lower limb. In total hip arthroplasty and total knee arthroplasty, the incidence ranges from 7% to 84%. In this study, the incidence and risk factors for postoperative urinary retention were described in a cohort of 376 men undergoing total hip arthroplasty. Postoperative urinary retention was defined as the inability to void after surgery for which single or indwelling catheterization was performed. Risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 18 publications
4
37
1
1
Order By: Relevance
“…Authors also revealed age of 70 years or older, spinal anesthesia, and postoperative patient -controlled analgesia were independent risk factors for POUR [9]. Higher incidence of POUR when compared with our study might be related to difference in surgical procedure performed or use of morphine sulfate during postoperative period, rather than paracetamol.…”
Section: Discussionsupporting
confidence: 47%
“…Authors also revealed age of 70 years or older, spinal anesthesia, and postoperative patient -controlled analgesia were independent risk factors for POUR [9]. Higher incidence of POUR when compared with our study might be related to difference in surgical procedure performed or use of morphine sulfate during postoperative period, rather than paracetamol.…”
Section: Discussionsupporting
confidence: 47%
“…Other strategies to reduce the risk of IDC‐related UTI in the peri‐operative setting include intermittent or no catheterization, early mobilization (that shortens the period when the IDC needs to remain in place), training for insertion techniques, good IDC care and consideration of IDC materials . Male patients receiving epidural anaesthesia may be at greater risk of urinary retention in the setting of orthopaedic surgery …”
Section: Discussionmentioning
confidence: 99%
“…33 Male patients receiving epidural anaesthesia may be at greater risk of urinary retention in the setting of orthopaedic surgery. [34][35][36] There were several limitations to our study. These included confounding factors that may influence SSI rates (skin preparation, surgical technique and patient comorbidities) and the significantly larger proportion of male patients in the post-intervention sample (probably resulting from variation in data collection methods).…”
Section: Studies Reporting Bacteraemiamentioning
confidence: 99%
“…Regional anesthesia is recommended for ERAS because it provides reliable analgesia and little disturbance on hemodynamics in published literatures [2,3,4,6]. However, for patients undergoing THA and TKA, spinal anesthesia is frequently associated with prolonged indwelling urinary catheter [7], and furthermore, the peripheral nerve block may weaken the lower limb muscle strength, leading to delayed mobilization [8].…”
Section: Introductionmentioning
confidence: 99%